G217(P) The burden of stoma-related complications in preterm infants. (12th March 2018) - Harris, L; Smee, N; Bradnock, T; Simpson, J; Granger, C
Abstract : Aims: Preterm infants requiring small bowel resection may receive a temporising enterostomy to divert the faecal stream and allow optimisation of their clinical condition and nutritional status prior to restoration of intestinal continuity. Facilitating growth in the presence of an enterostomy can be challenging, and may require adjuvant parenteral nutrition in addition to enteral feeds. There remains no consensus regarding the optimal timing of stoma closure. We aimed to determine the stoma-related complication rate in preterm neonates undergoing small bowel resection and enterostomy formation to help inform discussions about the timing of stoma closure. Methods: We retrospectively identified all infants<32 weeks gestation who underwent small bowel resection and enterostomy formation between January 2012 and June 2017, from our surgical procedures database. Information including basic demographics, indication for enterostomy, timing of formation and closure and associated complications were extracted from case records. Local Caldicott Guardian approval was obtained. Results: 34 neonates were identified with a median gestational age and birth weight of 27+3 weeks (range 23+2–31+6) and 933 grams (range 480–2050) respectively. Indications for enterostomy formation were necrotising enterocolitis (NEC) in 16 (47%) infants, spontaneous intestinal perforation in 9 (26%) and 'other' in 9 (26%). The overall median age at stoma formation was 26 days (range 3–97); with a median age of 44 days (range 6–71) in infants with NEC, compared to 15 days (range 3–97) for all other infants. Median age at stoma closure was 105 days (range 27–394). 27 neonates (79%) required adjuvant parenteral nutrition via central venous access and 14 (51%) of these developed a central line associated complication. There were 7 stoma-related complications comprising 3 stoma prolapse, 1 wound dehiscence and 3 superficial wound breakdown. Conclusions: Complications directly related to an enterostomy, or due to a requirement for central venous access and parenteral nutrition are common in preterm infants. These data should inform multidisciplinary discussion regarding the risks and benefits of persevering with an enterostomy versus early closure.